Analysis of Factors Influencing Capital Structure in Property and Real Estate Companies Listed on The Indonesia Stock Exchange - Dyta Anggraini; Warsono; Chalimatuz Sa'diyah (Universitas Muhammadiyah Malang, 2023)
This research aims to analyze the factors that influence the capital structure of property and real estate sector companies listed on the Indonesia Stock Exchange (BEI) in the 2016-2019 period. This analysis method uses quantitative research using multiple linear regression analysis. The research results show that of the 10 companies in the research sample, asset structure, profitability, and liquidity have a significant effect on the capital structure of property and real estate companies listed on the Indonesia Stock Exchange. Furthermore, asset structure has the greatest influence on the capital structure of property and real estate companies listed on the Indonesia Stock Exchange.